Directed sortase A evolution for efficient site-specific bioconjugations in organic co-solvents. Issue 81 (26th September 2018) - Zou, Zhi; Alibiglou, Hoda; Mate, Diana M.; Davari, Mehdi D.; Jakob, Felix; Schwaneberg, Ulrich
Abstract : Evolved sortase A variants enable efficient site-specific bioconjugations in organic co-solvents. Abstract : Directed sortase A evolution yielded the variants R159G and D165Q/D186G/K196V with increased resistance (2.2-fold) and catalytic efficiency (6.3-fold) in 45% (v/v) dimethylsulfoxide. Interestingly, D165Q/D186G/K196V also showed an up to 4.7-fold increased activity for the conjugation of hydrophobic peptides/amines in co-solvents. MD simulations revealed that conformational mobilities are important for the gained resistance.